MEDIA PEMBELAJARAN BERBASIS VIDEO MENGGUNAKAN POWTOON DAN MOVAVI VIDEO EDITOR TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA - Nina Mirawati; Pujia Siti Balkist; Ana Setiani (De Fermat : Jurnal Pendidikan Matematika, 2021)
Math learning has a finite amount of space and time. Where a junior high school math class in one grade is only a five-hour lesson with an hour lesson of only 40 menutes is considered insufficient. Apart from the lack of time for learning, there are a number of factors that are a barrier to math study, which is the influence of internal and external factor. On external factor such as the impact of the ingredients. Using a textbook is not enough for students to understand math lesson. For this reason research are trying to develop video-based teaching materials in hopes of overcoming space and time on learning. The learning video countains material discussions, examples of problems, discussion of examples problems, it’s been valeted by a material expert, so that the teaching materials developed by researchers can direct students to critical thinking. With the learning video, it is expected that students can learn anywhere and any time without the countraining of spcace and time. And the ultimate purpose of this video-based teaching development is to increase students critical thinking ability.